2023
DOI: 10.3390/pathogens12070943
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Streptococcus pneumoniae Detected in Hospitalized Pediatric Acute Respiratory Infection Cases in Central Vietnam

Abstract: Streptococcus pneumoniae is the major bacterial pathogen causing high pneumonia morbidity and mortality in children <5 years of age. This study aimed to determine the molecular epidemiology of S. pneumoniae detected among hospitalized pediatric ARI cases at Khanh Hoa General Hospital, Nha Trang, Vietnam, from October 2015 to September 2016 (pre-PCV). We performed semi-quantitative culture to isolate S. pneumoniae. Serotyping, antimicrobial susceptibility testing, resistance gene detection and multi-locus se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In some studies, some STs were found to be dominant. For example, the dominant STs were ST320, ST271, ST81, ST876, and ST3173 in China [ 19 ]; ST179, ST2918, ST386, and ST3772 in Tunisia [ 32 ]; ST320 and ST13223 in Vietnam [ 33 ]; ST618 and ST3081 in the Gambia [ 34 ]; and ST306, ST191, ST989, and ST180 in Spain [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, some STs were found to be dominant. For example, the dominant STs were ST320, ST271, ST81, ST876, and ST3173 in China [ 19 ]; ST179, ST2918, ST386, and ST3772 in Tunisia [ 32 ]; ST320 and ST13223 in Vietnam [ 33 ]; ST618 and ST3081 in the Gambia [ 34 ]; and ST306, ST191, ST989, and ST180 in Spain [ 35 ].…”
Section: Discussionmentioning
confidence: 99%